2014
DOI: 10.1007/s12041-014-0389-5
|View full text |Cite
|
Sign up to set email alerts
|

A substitution mutation in OsCCD7 cosegregates with dwarf and increased tillering phenotype in rice

Abstract: Dwarf plant height and tillering ability are two of the most important agronomic traits that determine the plant architecture, and have profound influence on grain yield in rice. To understand the molecular mechanism controlling these two traits, an EMS-induced recessive dwarf and increased tillering1 (dit1) mutant was characterized. The mutant showed proportionate reduction in each internode as compared to wild type revealing that it belonged to the category of dn-type of dwarf mutants. Besides, exogenous app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
2
20
1
Order By: Relevance
“…Nagina 22 is a well-known aus variety used routinely as a check for heat tolerance in rice (Jagadish et al, 2010). In a network project, EMS-induced stabilized N22 mutants were evaluated for different traits, such as tolerance to herbicide, heat, low P, water deficiency, and salinity and resistance to bacterial leaf blight and blast (Kulkarni et al, 2013(Kulkarni et al, , 2014Lima et al, 2015;Mithra et al, 2016;Mohapatra et al, 2014;Panigrahy et al, 2009Panigrahy et al, , 2011Panigrahy et al, , 2014Poli et al, 2013;Talla et al, 2016). As a part of the network project on functional genomics, a total of 2500 N22 mutants were screened at the Indian Institute of Rice Research (IIRR) under field conditions maintained with low P (Olsen P, <1.8) to identify low-P-tolerant and susceptible mutants.…”
mentioning
confidence: 99%
“…Nagina 22 is a well-known aus variety used routinely as a check for heat tolerance in rice (Jagadish et al, 2010). In a network project, EMS-induced stabilized N22 mutants were evaluated for different traits, such as tolerance to herbicide, heat, low P, water deficiency, and salinity and resistance to bacterial leaf blight and blast (Kulkarni et al, 2013(Kulkarni et al, , 2014Lima et al, 2015;Mithra et al, 2016;Mohapatra et al, 2014;Panigrahy et al, 2009Panigrahy et al, , 2011Panigrahy et al, , 2014Poli et al, 2013;Talla et al, 2016). As a part of the network project on functional genomics, a total of 2500 N22 mutants were screened at the Indian Institute of Rice Research (IIRR) under field conditions maintained with low P (Olsen P, <1.8) to identify low-P-tolerant and susceptible mutants.…”
mentioning
confidence: 99%
“…In spite of these, however, mapping of dit1 appears to suggest that to develop advanced segregating populations such as NILs or CSSLs is not always prerequisite for fine mapping of the genes underlying such a quantitative trait. In the mapping case of the EMS-induced dit1 allele for dwarf and increased tillering, the gene on chromosome 4 could explain 19.79% of tiller number variation in its F2 mapping population [14]. In this study, trait culm number was also found to show a continuous distribution in the ts1 /Wushansimiao F2 population.…”
Section: Discussionmentioning
confidence: 55%
“…In rice, tillering has been found to be quantitative in nature [14]. Tiller number trait tends to show a continuous distribution in a segregated population, which indicates that multiple genes or QTLs could be involved in its regulation.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Mutants of Loc_Os06g46470, including hdt1 and osccd7, exhibited similar phenotype with so1 (Kulkarni et al 2014;Zou et al 2006), we therefore concluded that the so1 phenotype is due to the 8bp insertion in Loc_Os04g46470.…”
Section: Genetic Analysis and Mapping Of So1supporting
confidence: 53%
“…HTD1 encodes a carotenoid cleavage dioxygenase involved in SL synthesis, which negatively regulates the growth of axillary buds (Kulkarni et al 2014;Zou et al 2006). However, whether and how HDT1 functions in other tissues was unknown.…”
Section: Discussionmentioning
confidence: 99%